STUDI PENYUSUNAN ZONA KERENTANAN AIR TANAH METODE GROUNDWATER, OCCURANCE, OVELAYING LITHOLOGY DEPTH OF GROUNDWATER (GOD) DI KOTA PEKALONGAN - Thomas Triadi Putranto; Novi Susanto; Nestri Martini (JURNAL LITBANG KOTA PEKALONGAN, 2022)
Environmental problems that arise are often triggered by the development of population and socioeconomic communities. The increase in population affects the water needs in Pekalongan City. Water needs in Pekalongan City are obtained from unconfined aquifers and confined aquifers. The quality of unconfined aquifer groundwater is more susceptible to pollution than confined aquifers. This is because the groundwater in the aquifer is close to the surface, allowing pollutant sources to easily enter the groundwater. One of the objectives of this study is to determine the level of vulnerability and its suitability with land use. This study used the GOD (Groundwater occurrence, Overlying lithology and Depth of groundwater) method, to analyze the vulnerability of groundwater to pollution. The parameters used consist of the type of aquifer, the type of cover lithology, and the grondwater depth of the unconfined aquifer. The three parameters were analyzed using a Geographic Information System (GIS) and a raster overlay was performed. From the results of the analysis, it produced 3 (three) zones, namely moderate vulnerability level (0.45-0.5), high vulnerability (0.51-0.7), and very high vulnerability level (0.71-0.9). Keywords: Unconfined Aquifer, GOD, groundwater vulnerability zone, Pekalongan City.